Determinants of R&D Activity - Analysis of the Polish Logistics Sector (Economic and Political Thought, 2018)
The aim of the article is to identify factors that significantly affect the levelof R&D and to determine the strength of this impact. The research involved950 Polish logistics companies. Data from the Local CSO Data Bank from2007–2015 were used for the study. As explanatory variables, three groupsof potential R&D determinants of the studied entities were distinguished:intensity of competition, financial performance of the enterprise andmacroeconomic conditions. The analysis was based on descriptive statistics,Pearson’s correlation analysis and Spearman’s rank correlation coefficientand the use of panel models, estimated on the basis of a cross-sectionalsample. The statistical survey was carried out both on aggregate nationalvalues and using data at the voivodship level. The study showed that R&Dactivities of logisticsfirms are carried outprimarily by larger companies, whichconduct a conservative financing policy based on low indebtedness and highliquidity.These firms operate in a low marginenvironment, which significantlylimits development opportunities. The study did not confirm the impact ofcompetition on R&D activity, which may result from the growth of the sectoritself. However, the availability of road infrastructure and urbanized areas isa factor that indisputably affects R&D.
Keywords: research and development, logistics, company, Poland